Did the screens win? An autoregressive model linking leisure, relatedness and mental health. (July 2021) - Vacchiano, Mattia; Valente, Riccardo
Abstract: While it is well known that sport and exercise are beneficial for physiological and neurological functioning, leisure has received less attention as a means of mobilizing social networks and cultivating relatedness as factors protecting mental health. Using a sample of 8148 cases from the Swiss Household Panel (SHP), we built an autoregressive cross-lagged model to determine how offline and online leisure is related to perceptions of support from relatives and friends (relatedness), and with an indicator of psychological distress across a span of three years (2015–2018). Our findings show that pre-existing psychological distress leads to greater engagement in online leisure, such as browsing the Internet and online chatting, which is alleged to be due to social anhedonia. However, we do not find evidence that screen-use activities per se lead to mental distress over time. By contrast, engagement in both offline leisure and face-to-face interactions appears to be a key mechanism in activating those processes of social capital mobilization that help cultivate feelings of relatedness and are associated with better mental health. These findings suggest that more attention is needed to distinguish those who avoid engagement in face-to-face interactions from screen-users per se. Hopefully, this will stimulate the creation of novel theoretical frameworks capable of addressing this subject during the global pandemic, in which computers are playing a crucial role in maintaining social ties. Highlights: Pre-existing psychological distress leads to greater engagement in online leisure. Offline leisure has a greater impact than online leisure on relatedness. Feelings of relatedness are associated with better mental health. No evidence was found that screen-use activities lead to mental distress over time.